(3JbfjGJ EfJGL GdehGO GdSeYjI GdHUQjI h GSJNOGegG (B/s - (3eUHGM, GdMGL YjSis; (3eMeO PjHGf(B;(3EjGO CMeO(B;(3Jhajb CMeOs ((3LGeYI GdchjJ (B:s (3LGeYI GdchjJ ,s, 1990)
(3GMJhi gPG GdcJGH Ydi GQHY hMOGJ JOQjSjI gj GdJUhjQ GdahJhZQGaj GdTQGFM h GdGadGe GdKGHJI hSGFd GdGJUGd GdSeYjI h SGFd GdGJUGd GdSeYjI GdHUQjI s
(3HHdjhZQGajG (B: (3U(B.391-394s
Keywords: (3GdSeYj GdHUQjs; (3hSGFd GdGJUGds; (3GdCadGes; (3GdJUhjQ GdahJhZQGajs